ANALYSIS OF THE WORK ENVIRONMENT IN IMPROVING EMPLOYEE PERFORMANCE PT PLN (PERSERO) ULTG PANAKKUKANG - Justina, Justina; Agus Salim; Nurinaya, Nurinaya (International Journal of Economic Research and Financial Accounting, 2024)
This study aims to determine the exact analysis of the work environment in improving the performance of employees of PT PLN (Persero) ULTG Panakkukang. This type of research is qualitative. The type of data used is descriptive qualitative with data collection through observation and interviews. The object of this research is the manager and employees of PT PLN (Persero) ULTG Panakkukang, totaling five people. The results of the research that can be written show that the non-physical work environment at PT PLN (Persero) ULTG Panakkukang is inadequate It is said to be inadequate because communication between coworkers is less harmonious. The factor for the lack of communication at PT PLN (Persero) ULTG Panakkukang is the fatigue factor or work pressure factor. The physical work environment at PT PLN (Persero) ULTG Panakkukang is not ideal as there are still some office facilities that have not been fulfilled and this affects the work environment of employees and will have an impact on the survival of the company